Pathology of Black Creek Canal Virus Infection in Juvenile Hispid Cotton Rats (Sigmodon hispidus) - Billings, Adrian N. (Mary Ann Liebert, Inc., 2010)
The purpose of this study was to assess the effect of inoculum dose on the pathogenesis of Black Creek Canal virus (BCCV) infection in the hispid cotton rat (Sigmodon hispidus), the principal host of BCCV. No sign of illness was observed in any of the 52 juvenile hispid cotton rats inoculated with 3.1, 1.1, −0.9, or −2.9 log(10) median infectious doses(VeroE6) (ID(50-VeroE6)) of BCCV and euthanized on day 9, 18, 27, or 54 postinoculation (PI). Analysis of virus assay and serological data indicated that inoculum dose could significantly affect the pathogenesis of BCCV infection in juvenile hispid cotton rats. For example, the six animals inoculated with 3.1 or 1.1 log(10) ID(50-VeroE6) and euthanized on day 54 PI were virus positive and antibody positive, whereas the six animals inoculated with −0.9 or −2.9 log(10) ID(50-VeroE6) and euthanized on day 54 PI were virus positive but antibody negative. Microscopic examination of tissues from the animals inoculated with 3.1 or 1.1 log(10) ID(50-VeroE6) revealed diffuse, subacute pneumonitis in the lungs of all the animals euthanized on day 18 PI or thereafter, and indicated that the severity of pneumonitis was dependent upon inoculum dose as well as duration of infection (i.e., amount of time elapsed since inoculation).